2004
DOI: 10.1097/01.asn.0000114554.67106.28
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of TNFα Blockade with Infliximab in Anti-Neutrophil Cytoplasmic Antibody-Associated Systemic Vasculitis

Abstract: Abstract. Tumor necrosis factor ␣ (TNF␣) plays an important role in the pathogenesis of anti-neutrophil cytoplasmic antibody-associated systemic vasculitis. TNF␣ blockade is a potential therapy for these disorders. Methods: An open-label, multi-center, prospective clinical trial in two subgroups was performed. Study I examined acute disease, either first presentation or relapse (Birmingham Vasculitis Activity Score [BVAS] Ն 10; n ϭ 16); study II examined persistent disease (BVAS Ն 4; n ϭ 16). Patients received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
166
0
8

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 334 publications
(179 citation statements)
references
References 23 publications
5
166
0
8
Order By: Relevance
“…Ten of 14 patients with active disease agreed to enter an established clinical pilot study, 20 in which patients received 5 infusions of the human-mouse chimeric monoclonal antibody infliximab, directed against TNF-␣ (5 mg/kg) at 0, 2, 6, and 10 weeks. Infliximab was given either alone (nϭ6) to patients receiving stable prednisolone doses (unchanged for a month) and mycophenolate mofetil or in addition to standard induction therapy of prednisolone and cyclophosphamide (nϭ4).…”
Section: Study 2: Effects Of Treatment On Endothelial Functionmentioning
confidence: 99%
“…Ten of 14 patients with active disease agreed to enter an established clinical pilot study, 20 in which patients received 5 infusions of the human-mouse chimeric monoclonal antibody infliximab, directed against TNF-␣ (5 mg/kg) at 0, 2, 6, and 10 weeks. Infliximab was given either alone (nϭ6) to patients receiving stable prednisolone doses (unchanged for a month) and mycophenolate mofetil or in addition to standard induction therapy of prednisolone and cyclophosphamide (nϭ4).…”
Section: Study 2: Effects Of Treatment On Endothelial Functionmentioning
confidence: 99%
“…In different dosage (3mg/kg in 2 patients and 5 mg/kg in 4 patients), the addition of infliximab to standard therapy achieved remission in five out six patients, being discontinued in the remaining one due to a non-confirmed infection. In another study (Booth et al, 2004), an open-labelled multicenter non-controlled trial, infliximab was associated with a high rate of remission (88% patients in about 6 weeks) in 28 patients with Wegener granulomatosis and microscopic polyangiitis. Disease activity scores, inflammatory markers and prednisolone but high rate of relapses after discontinuation and intolerable severe adverse events (especially infections and increased risk of malignancies -found with etanercept) make anti-TNF agents not formally recommended for the management of ANCA-associated vasculitis.…”
Section: Tnf Blockadementioning
confidence: 99%
“…In addition to conventional immunosuppressants, infliximab was administered at 3-5 mg/kg at intervals of 4-8 weeks, resulting in induction of remission in 43 (81%). Booth, et al, 9) reviewing 32 cases, reported that remission could be achieved very early, i.e., a mean of 6.4 weeks after the introduction of infliximab. In the 33 cases followed up for 1 year or longer, remission could be maintained for 6 months or longer in 28 (85%), and reactivation after remission was observed in 5 (12%).…”
Section: Usefulness Of Infliximab For the Treatment Of Anca-associatementioning
confidence: 99%
“…However, 4 open pilot studies have been reported along with case reports suggestive of its usefulness. [6][7][8][9] Of the 54 cases included in the 4 reports, 35 had Wegener's granulomatosis, and 16 had microscopic polyangiitis. Thirty-seven of the 54 cases were refractory cases in which remission could not be induced by a standard immunosuppressive therapy.…”
Section: Usefulness Of Infliximab For the Treatment Of Anca-associatementioning
confidence: 99%